Spontaneous coronary artery dissection : Case series from two institutions with literature review (2015)
ABSTRACT: Spontaneous coronary artery dissection (SCAD) is a rare cause of acute coronary syndrome (ACS). Consequently, its presentation and optimal treatment are yet to be clearly defined. In the current literature, all case series report less than 50 patients, most of whom are either young peripartum women or women who have used oral contraceptives over long periods. All information in this study was compiled by the database service from two hospitals, the first one between 2003 and 2012 and the second one between 2007 and 2012, to include the clinical characteristics, angiography, and treatment approaches in the study population. The study population consisted in four women (50%) and four men (50%) whose ages ranged between 28 and 57 years. Two women had a history of oral contraceptive use and three women presented during peripartum. None of the patients had traditional cardiovascular risk factors or previous heart disease. In 88% of the cases, the principal diagnoses were non-ST segment elevation myocardial infarction and unstable angina. All patients underwent emergency coronary angiography and percutaneous coronary intervention. Half of them were treated with drug-eluting stents and the other half with bare metal stents. The most frequent type of dissection was NIHBL Type E, and the right coronary artery was the most frequently compromised. SCAD is a rare cause of ACS; however, its identification has improved due to the availability of angiography and new complementary techniques. Regarding treatment, PCI seems effective with adequate long-term results.